2021
DOI: 10.1111/apt.16550
|View full text |Cite
|
Sign up to set email alerts
|

Review article: current and future treatment approaches for pain in IBS

Abstract: SummaryBackgroundAbdominal pain is a core symptom of IBS and a primary driver of care seeking. Visceral hypersensitivity is a key pathophysiological mechanism and therapeutic target for pain in IBS, with components of peripheral and central sensitisation and psychological factors.AimTo review current and future treatment approaches specifically for the pain component of IBS.MethodsPubmed search terms included combinations of irritable bowel, pain, visceral hypersensitivity, novel, new, emerging, future and adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 156 publications
(143 reference statements)
0
21
0
Order By: Relevance
“…Indeed, hypersensitivity together with an impaired gas transit and evacuation might generate symptoms such as pain and bloating 44 . However, the exact cause of visceral hypersensitivity has not been elucidated yet, even though central and peripheral sensitization, allodynia and hyperalgesia, together with psychological factors have been implicated in its genesis 7 . Indeed, it has been recently shown by fMRI that brains of IBS patients respond differently to fructan infusion in areas related to pain, such as the cerebellum, supramarginal gyrus, anterior and midcingulate cortex, insula and thalamus, highlighting the importance of a dysfunctional gut‐brain axis in IBS 45 .…”
Section: Mechanisms Underlying Efficacy Of a Low Fodmap Dietmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, hypersensitivity together with an impaired gas transit and evacuation might generate symptoms such as pain and bloating 44 . However, the exact cause of visceral hypersensitivity has not been elucidated yet, even though central and peripheral sensitization, allodynia and hyperalgesia, together with psychological factors have been implicated in its genesis 7 . Indeed, it has been recently shown by fMRI that brains of IBS patients respond differently to fructan infusion in areas related to pain, such as the cerebellum, supramarginal gyrus, anterior and midcingulate cortex, insula and thalamus, highlighting the importance of a dysfunctional gut‐brain axis in IBS 45 .…”
Section: Mechanisms Underlying Efficacy Of a Low Fodmap Dietmentioning
confidence: 99%
“…Thus, dietary interventions are often proposed by clinicians or self‐administered by patients as initial therapeutic approaches to curb IBS symptoms. A diet low in fermentable oligosaccharides, disaccharides, monosaccharides, and polyols (FODMAPs) is now considered by many a first‐line treatment option for IBS 7 . Despite growing number of randomized clinical trials assessing the efficacy of a low FODMAPs diet in reducing IBS symptoms, the quality of the evidence has been questioned, due to the likely presence of bias in dietary intervention trials 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive behavioral gut-brain targeted treatment has gained popularity with improved symptom outcomes as well as self-help workbooks and apps [5,6]. Current treatment models developed around the growing acceptance of the gut-brain connection use hypnosis and cognitive therapy as key attributes to improving visceral hypersensitivity [23,24].…”
Section: Qualitative Study Designs -Personal Experiences and Improved...mentioning
confidence: 99%
“…While it was shown that an imbalanced and nutritionally deficient diet could promote, maintain, and worsen IBS symptoms [13], several studies have documented significant improvement in IBS symptomatology directly correlated with changes in dietary habits [14][15][16][17][18]. The FODMAP diet is just one of the current food plans used to alleviate IBS gastroenterological symptoms by assessing each aliment's implications following the IBS patient's tolerance to it or its benefits [19].…”
Section: Introductionmentioning
confidence: 99%